Strategy of the Majalengka Regency Tourism and Culture Office in Promoting Paragliding Tourism Destinations - Prahastuti Yasmin; Mochammad Fauzul Haq; Rafiuddin Akil (COMMENTATE: Journal of Communication Management, 2021)
This research is backgrounded by the huge potential of tourism sector in Majalengka but in fact it cannot be maximized by the government. One of the most popular tourist destinations this time is Paragliding. Although the promotion has been carried out by the local government through tourism and cultural office of majalengka, even it has been covered by national TV stations, but still the visit to paragliding is only dominated by local tourists. This is a problem because paragliding tourist destination is like march in place  even though the promotions have been made. This study explored using marketing communication theory that focuses on 5 dimensions of the promotion mix, namely: advertising, direct marketing, personal selling, sales promotion, and public relations. In addition, the concept of promotion strategy that divides into two types, namely: push strategy and pull strategy is used to determine the promotion strategy applied by the tourism and culture office of Majalengka. The concept of tourist destinations that focuses on 5 variables: attraction, accessibility, amenities, ancillary services, and institutions are used to explore paragliding tourism destination itself. The research was carried out with a qualitative methodology of constructivism paradigm. The results showed that the tourism and culture department of Majalengka did not run maximally the promotion mix as it should be, advertising was not carried out continuously and periodically, public relations was not conducted, direct marketing was still done in traditional ways such as the use of pamphets and CDs.